INTERACTIVE WORK PLACE TRAUMA (IWPT) “A Pervasive Condition Requiring Immediate Isolation and Treatment” - Shewchuk, Muriel (Operating Room Nurses Association of Canada Journal, 2005)
How much Interactive Work Place Trauma, or IWPT*, has invaded your perioperative environment and is lurking in the corners, lounges, and theatres... or even exuding from your office? Who is involved? Nurses, support staff, physicians, or leaders? Or a combination of all? Do you know about it? Are you demonstrating ostrich characteristics by “sticking your head in the sands of denial”? Denial and wishful thinking will not cut-it! * Interactive Workplace Trauma (IWPT) is a term coined by the author for purpose of this article.